Teacher Engagement in Language Teaching: Investigating Self-Efficacy for Teaching Based on the Project “Sino-Greece Online Chinese Language Classrooms” - Bao, Chunrong; Zhang, Lawrence Jun; Dixon, Helen R. (Frontiers in Psychology, 2021)
The support of Sustainable learning of foreign languages requires teacher engagement and a high level of self-efficacy, both of which are cornerstones for teachers’ persistence in carrying out the teaching activity intended to help learning. The need for such attributes are even more critical when teaching using online learning platforms, mode of delivery becoming increasingly popular. We would argue that keeping students engaged and motivated to attain their academic success online calls for teachers’ increased levels of resilience and effort. Although teachers’ self-efficacy has been widely considered crucial in teachers’ professional practices, there is a paucity of research on the self-efficacy of teachers who teach Chinese as a foreign language (CFL) using online platforms. Such a gap becomes prominent after the sudden outbreak of COVID-19 pandemic, where there are now numerous calls for online CFL classes. In order to fill in this gap, this study was conducted with a frontline CFL teacher as the participant, aiming to detect thoroughly the trajectories of a CFL teacher’ self-efficacy in the completely new teaching context. Embedded in the Project of Sino-Greece Online Chinese Language Classroom, this study employed narrative inquiry and case study as methodological approaches. Thematic analysis was used to analyze the data which consisted of written narratives (the teacher’s written teaching journals and reflections, teaching assistant’s field notes, and students’ emails) and spoken narratives. Three research questions guide this study: What are the teacher’s beliefs about (1) the opportunity of teaching CFL online? (2) the management of this online project? (3) her teaching ability in this project? These three questions focus respectively on the three components of teacher’s self-efficacy system (personal efficacy, efficacy within the organization, professional efficacy) (Friedman & Kass, 2000; Sela-Shayovitz & Finkelstein, 2020; Wang, Hall & Rahimi, 2015). Findings illustrate that the teacher’s efficacy beliefs in these three aspects were at different levels, which resulted from the interplay of external and internal factors; when external factors appeared to be negative, the internal factors would play an essential role.